2022
DOI: 10.1109/access.2022.3232036
|View full text |Cite
|
Sign up to set email alerts
|

Signal Preprocessing Technique With Noise-Tolerant for RF-Based UAV Signal Classification

Abstract: Since the beginning of the COVID-19 pandemic, the demand for unmanned aerial vehicles (UAVs) has surged owing to an increasing requirement of remote, noncontact, and technologically advanced interactions. However, with the increased demand for drones across a wide range of fields, their malicious use has also increased. Therefore, an anti-UAV system is required to detect unauthorized drone use. In this study, we propose a radio frequency (RF) based solution that uses 15 drone controller signals. The proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Experimental results in [19] showed that the proposed hierarchical learning approach has outperformed other techniques with an accuracy rate of 0.99. Convolution neural network (CNN) has been utilized in [20] to develop a noise immune UAV signal classification system which has been tested at different signal-tonoise ratios (SNRs). Support vector machine (SVM), artificial neural network (ANN), decision tree (DT), and random forest (RandF) classifiers have been utilized in [21] for detection and classification of drones in the presence of Wi-Fi interference using UAV video signal (VS) fingerprints where indoor and outdoor experiments have been carried out with high accuracy rates, especially by using RandF.…”
Section: A Related Work 1) Rf-based Uav Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results in [19] showed that the proposed hierarchical learning approach has outperformed other techniques with an accuracy rate of 0.99. Convolution neural network (CNN) has been utilized in [20] to develop a noise immune UAV signal classification system which has been tested at different signal-tonoise ratios (SNRs). Support vector machine (SVM), artificial neural network (ANN), decision tree (DT), and random forest (RandF) classifiers have been utilized in [21] for detection and classification of drones in the presence of Wi-Fi interference using UAV video signal (VS) fingerprints where indoor and outdoor experiments have been carried out with high accuracy rates, especially by using RandF.…”
Section: A Related Work 1) Rf-based Uav Detectionmentioning
confidence: 99%
“…where ϵ is the weighting factor that represent the contribution of H 1 on Ψ such that 0 < ϵ < 1. Therefore, the expression of the suboptimal threshold under the LoS channel state, η L , can be expressed using (20) as…”
Section: Proposed Low-complexity Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen from the relevant studies that all types of studies show a relatively complete research system, and the relevant recent studies have been organized in detail in [28].…”
Section: Radio Detectionmentioning
confidence: 99%
“…Although the proposed approach is based on timedomain 250 µs signal segments with minor input signal processing, it has the potential to achieve high accuracy and be used in portable real-time systems while having a relatively low level of complexity. In contrast, to increase accuracy in low SNR conditions, special preprocessing techniques are applied to the time-frequency signal representation in [33] prior to utilising DL. The method's findings imply that distinguishing using the spectrogram is more accurate, however, the classification of multiple drone controller signals remains challenging.…”
Section: Related Workmentioning
confidence: 99%